Synthesis and reactivity of 9, 10-bis(4-trimethylsilylethynylbuta-1, 3-diynyl)anthracene derived chromophores. Issue 14 (16th March 2023) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract : 9, 10-Bis(4-trimethylsilylethynyl-butadiynyl)anthracene serves as a convenient building block for the construction of new butadiynyl and hexatriynyl anthracenes terminated by metal complexes, arenes, haloarenes and alkynyl functionalities. Abstract : 9, 10-Bis(4-trimethylsilylethynylbutadiynyl)anthracene is readily availabe from the reaction of anthraquinone and LiCCCCSiMe3 followed by reduction with Sn(ii ) and serves as a convenient building block via desilylation and palladium-mediated C–C coupling processes for the construction of further butadiynylanthracenes terminated by metal complexes, arenes, haloarenes and alkynyl functionalities.